Estado actual de comercialización de madera aserrada y valor agregado, en depósitos ubicados en el área metropolitana de la ciudad de Iquitos – 2022 - Casique Murayari, Jose Miguel (2024)
The present study was carried out in the Wood and value-added warehouses established in the metropolitan city of Iquitos, with the purpose of knowing the current state of the warehouses that sell sawn wood and value-added located in the metropolitan área of the city of Iquitos. From the obtained results, there are 101 commercial establishments dedicated to the sale of sawn wood recognized by the competent authority (GERFOR), of which 57% are located in San Juan district, 27 in Iquitos, 12% in Punchana and 4% in Belen district. 12 species such as pashaco, tornillo, quillosisa, quillabara, requia, catahua, marupa cedro, moena, capinuri, cumala are marketed in larger volumes; as well as other products with added value, in low volumes and in other cases simply in the natural state. The quality of the wood is oflow quality and corresponds in a high percentage to third quality woods and rejections. The companies are 100% legal, they are registered in SUNAT and GERFOR, but there is a high percentage of informality. The estimated sales volumen of sawn wood is 8,840,393 pt with an amount in soles of S/. 14,976,000. There are various wood substitute products that are lowering the consumption levels of organic wood.